Analysis of Factors that Influence Consumers’ Trust to Use AI Service: The Case of Mandiri Bank’s MITA Chatbot - Naura Fitri Nisa; Arif Hartono (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The use of chatbots has seen rapid development across various sectors in recent years, including in the banking industry. This study evaluated and examined the relationship between factors that influence consumer trust in the use of the AI chatbot service, MITA, at Mandiri Bank. The importance of conducting this research lies in answering questions regarding the key factors that affect users' or customers' trust in chatbots, such as perceived benefits and ease of use, which influence the intention to adopt new technologies, particularly Mandiri Bank’s MITA services. A total of 266 survey samples were collected from users of the Mandiri Bank’s MITA chatbot via an online survey, using convenience sampling for sample selection. The statistical analysis technique used in this study was Partial Least Squares Structural Equation Modeling (PLS-SEM) through the SmartPLS software. This study shows that perceived usefulness and user comfort do not have a significant effect on user trust in Mandiri Bank’s MITA chatbot. However, other factors positively and significantly affected user trust in the MITA chatbot. This study is expected to encourage marketing managers to explore more broadly and deeply how to build user trust in the banking industry and its future implications